2021
DOI: 10.3389/fneur.2021.628045
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Borrelia Spirochetes: A Case Study With Validation Among Autopsy Specimens

Abstract: The complex etiology of neurodegenerative disease has prompted studies on multiple mechanisms including genetic predisposition, brain biochemistry, immunological responses, and microbial insult. In particular, Lyme disease is often associated with neurocognitive impairment with variable manifestations between patients. We sought to develop methods to reliably detect Borrelia burgdorferi, the spirochete bacteria responsible for Lyme disease, in autopsy specimens of patients with a history of neurocognitive dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…While the Netherlands study also showed no significant difference between longer term treatment of patients with chronic symptoms and short-term therapy, the inclusion criteria were less stringent, potentially allowing patients without LD into the study. More recently, spirochetes were detected in post-mortem brain samples collected from a patient who previously was diagnosed and treated for LD and subsequently experienced chronic symptoms, including dementia (266).…”
Section: Persistent Infectionmentioning
confidence: 99%
“…While the Netherlands study also showed no significant difference between longer term treatment of patients with chronic symptoms and short-term therapy, the inclusion criteria were less stringent, potentially allowing patients without LD into the study. More recently, spirochetes were detected in post-mortem brain samples collected from a patient who previously was diagnosed and treated for LD and subsequently experienced chronic symptoms, including dementia (266).…”
Section: Persistent Infectionmentioning
confidence: 99%
“…Gadila et al 133 reported the case of a woman with a history of Lyme disease who secondarily developed dementia clinically consistent with DLB. After her death, analyses of brain and spinal cord tissues confirmed the presence of pathological markers of DLB and identified persistent Borrelia burgdorferi using PCR and immunofluorescence staining, raising the question of whether Borrelia may trigger the onset of DLB.…”
Section: Do Studies In Humans Incriminate a Particular Pathogen?mentioning
confidence: 99%
“…Imaging was performed using a Nikon Ti2-E motorized fluorescence microscope [52]. Infected and uninfected cells were imaged during the same session with identical acquisition parameters.…”
Section: Immunofluorescence Assaymentioning
confidence: 99%